Dharma dan Geothermal: Menimbang Kewajiban Etis Terhadap Alam di Manggarai - Guru, Wilfridus; Jeruma, Yulianus Jimi; Purnama, Paskalis Ronal (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
With the development of the times, the need for electrical energy is also increasingly needed. The importance of electrical energy needs for the community makes the state think long to find a solution. One of the solutions used by the government is to utilize geothermal energy to meet the electricity needs of the community. This is what the local government of Manggarai, East Nusa Tenggara has done by utilizing geothermal energy in the Poco Leok Region and building a geothermal project. However, while the utilization of geothermal energy continues to be echoed, an important question arises in the minds of the community, is this geothermal project not bad for the community and nature? Through this paper, we try to examine more deeply the geothermal project in Manggarai and relate it to the concept of Dharma in Eastern Philosophy. The purpose of writing this article is to look at and explore the concept of Dharma in Eastern philosophy and relate it to the geothermal development project in Manggarai. The concept of Dharma, which provides guidelines for ethical obligations towards nature, can be a material for reflection in the development of geothermal projects. This paper uses the literature method by utilizing books, journals, magazines, and newspapers that discuss geothermal projects in Manggarai.